Efficient Adsorption of Super Greenhouse Gas (Tetrafluoromethane) in Carbon Nanotubes - Kowalczyk, Poitr; Holyst, R. (American Chemical Society, 2008)
Light membranes composed of single-walled carbon nanotubes(SWNTs) can serve as efficient nanoscale vessels forencapsulation of tetrafluoromethane at 300 K and operatingexternal pressure of 1 bar. We use grand canonical Monte Carlosimulation for modeling of CF4 encapsulation at 300 K andpressures up to 2 bar. We find that the amount of adsorbedCF4 strongly depends on the pore size in nanotubes; at 1 bar themost efficient nanotubes for volumetric storage have size R)0.68nm.This size corresponds to the (10,10) armchair nanotubesproduced nowadays in large quantities. For mass storage(i.e., weight %) the most efficient nanotubes have size R )1.02 nm corresponding to (15,15) armchair nanotubes. They arebetter adsorbents than currently used activated carbons andzeolites, reaching˜2.4molkg-1 ofCF4,whereas,the best activatedcarbon Carbosieve G molecular sieve can adsorb 1.7 molkg-1 of CF4 at 300 K and 1 bar. We demonstrate that the highenthalpy of adsorption cannot be used as an only measureof storage efficiency. The optimal balance between the bindingenergy (i.e., enthalpy of adsorption) and space available forthe accommodation of molecules (i.e., presence of inaccessiblepore volume) is a key for encapsulation of van der Wallsmolecules. Our systematic computational study gives the cleardirection in the timely problem of control emission of CF4 andother perfluorocarbons into atmosphere.